War stories : the causes and consequences of public views of war - Baum, Matthew A., 1965- (Princeton University Press, 2010)
How does the American public formulate its opinions about U.S. foreign policy and military engagement abroad? War Stories argues that the media systematically distort the information the public vitally needs to determine whether to support such initiatives, for reasons having more to do with journalists' professional interests than the merits of the policies, and that this has significant consequences for national security. Matthew Baum and Tim Groeling develop a "strategic bias" theory that explains the foreign-policy communication process as a three-way interaction among the press, political